CONTEXTUAL TEACHING LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SD N 2 BARENGLOR KECAMATAN KLATEN UTARA - Putri Zudhah Ferryka; Isna Rahmawati, Tukiyo (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article analyzes elementary school students’ low learning outcomes because the teaching process applied by teachers is monotonous, it is due to the application of conventional teaching methods. The teacher selected this method because of the convenience of implementation. The research in this article is to find out the contextual teaching-learning model to improve student’s learning outcomes at grade IV. The type of research is Classroom Action Research (CAR) with data collection techniques, tests, and non-test. The subjects involved 28 fourth-grade students at SDN 4 Barenglor Klaten in the academic year 2020/2021. Students’ learning outcomes at SDN 2 Barenglor have increased. It can be seen from the average score in the pre-test, which was 65.4, then in Cycle I it increased to 74.3, and in Cycle II it increased more to 78.7. The percentage of students’ learning outcomes in the pre-test is 25%, then in Cycle I it increased to 60.71%, and in Cycle II it increased more to 78.57%. Keywords: , students’ learning outcome, elementary school.